Características biológicas do peixe amazônico Cichla piquiti (Cichlidae:Perciformes) introduzido no reservatório de Cachoeira Dourada no rio Paranaíba, Brasil - Luiz, Tatiane Ferraz (Universidade Federal de São Carlos, 2010)
The Basin of the river Tocantins-Araguaia is the natural habitat of the Cichla piquiti species, however, currently it meets widely distributed in dams of the river Paraná especially in the Minas Gerais and São Paulo states. In these subject to flooding plain ecosystems, the trophic ecology of the communities of fish is influenced by some factors that can be modified by the dams, promoting great alterations in the biological interactions inside of environments. Therefore, the study of the alimentary specter of tucunaré Cichla piquiti, congregated to the knowledge gotten concerning the reproductive aspects of the population structure can contribute to evaluate the current condition of the species in the environment and, still, to provide information that can be used in the handling of other native species. The Cachoeira Dourada reservoir is located in the South America, central region of Brazil, whose geographic coordinates are 18°30' 11.47" S, 49°29' 18.78" and 18°34' 5.27" S, 49°19' 52.07". The collections had been carried through during 1 year, with aid of batteries of nets of wait which meshes that vary of 1,5 the 10,0 cm between adjacent us. Of the units they had been gotten total length, standard length, and all up weight. The stomachs had been weighed, fixed in formaldehyde 4% and the stomacal content was analyzed in stereo microscope, having written down itself it frequency of occurrence of the different item. The present work evidenced that it does not have natural predators and competitors in the environment and that the species have long reproductive period, with size of first maturation (L50) reduced in relation to other species of the sort. Successful establishments in environments with raised antropic influence, where the ecological relations had been reduced drastically, would have to cause modifications in the composition of all the local community. Nonetheless, in the reservoir made study, this appears to be a degree of slowing of the functions of this species with other native carnivorous fish, which could be supported by the wide variety, of foraging fish in the reservoir.
Keywords: Ecologia da população; Peixes - alimentação; Espécies invasoras; Estrutura populacional; Maturação - comprimento; Peixes - reprodução; CIENCIAS BIOLOGICAS::ECOLOGIA